A 10 J shock impedance in sinus rhythm correlates with a 65 J defibrillation impedance during subcutaneous defibrillator implantation using an intermuscular technique. (28th September 2021) - Okabe, Toshimasa; Savona, Salvatore J.; Matto, Faisal; Ward, Chad; Singh, Prabhpreet; Afzal, Muhammad R.; Kalbfleisch, Steven J.; Weiss, Raul; Houmsse, Mahmoud; Augostini, Ralph S.; Hummel, John D.; Daoud, Emile G.
Abstract: Introduction: Defibrillation testing (DT) is recommended during the subcutaneous defibrillator (S‐ICD) placement. We sought to compare 10 J shock impedance in sinus rhythm (SR) with 65 J defibrillation impedance and evaluate device position on a postimplant chest X‐ray (CXR) using an intermuscular (IM) technique. Methods: Consecutive S‐ICD implantations between 12/2019 and 12/2020 at The Ohio State University were reviewed. All implantations were performed using a two‐incision IM technique. Standard DT with 65 J shock and 10 J shock in SR were performed unless contraindicated. The PRAETORIAN score was calculated based on CXR. Results: A total of 37 patients (age: 47.2 ± 15.8 years old, male: n  = 26 [70.3%], body mass index: 30.1 ± 6.7 kg/m 2 ) underwent IM S‐ICD implantation, and of those, 27 (73%) underwent both 65 J shock and 10 J shock in SR. The coefficient of determination ( R 2 ) between 10 J shock impedance and 65 J shock impedance was 0.84. The mean of an impedance difference was 1.6 ± 4.8 Ω (minimum – 11 and maximum 8). Postimplant CXR was available for 33 out of 37 patients (89.2%). The PRAETORIAN score was less than 90 in all patients and the mean score was 32.7 ± 8.8. Conclusion: We demonstrated that 10 J shock impedance in SR correlated well with 65 J defibrillation impedance during IM S‐ICD implantation. An IM implantation technique provides excellent generator location on postimplant CXR. The IM technique combined with 10 J shock in SR may be sufficient to predict and ensure the defibrillation efficacy of the S‐ICD.